What Does 'Entrepreneurship' Data Really Show? - Acs, Zoltan J.; Desai, Sameeksha; Klapper, Leora F. (2012)
In this paper, we compare two datasets designed to measure entrepreneurship: The Global Entrepreneurship Monitor (GEM) dataset and the World Bank Group Entrepreneurship Survey (WBGES) dataset. We find a number of important differences when the data are compared. First, GEM data tend to report significantly higher levels of early stage entrepreneurship in developing economies than do the World Bank business entry data, while the World Bank business entry data tend to be higher than GEM data for developed countries. Second, we find that the magnitude of the difference between the datasets across countries is related to the local institutional and environmental conditions for entrepreneurs, after controlling for levels of economic development. Our findings suggest that entrepreneurs in developed countries have greater ease and incentives to incorporate, both for the benefits of greater access to formal financing and labor contracts, as well as for tax and other purposes not directly related to business activities.